Innovative Methods of Forming Students' Digital Learning Skills - Zilola Normurodovna Haydarova (Researchparks Publishing, 2023)
In this article, the innovative methods of forming digital learning skills in the educational process, teaching based on modern methods of digital teaching, and the analysis of the formation of skills and competencies in students are discussed.